Pengaruh Employee Engagement Dan Kepuasan Kerja Terhadap Organizational Citizenship Behaviour (OCB) Di Mediasi Oleh Intention To Stay Pada Malut Post Kota Ternate - Malik, Fitri Yanti Abd; Marwan, Marwan; M. Alhadar, Fadliah (Faculty of Economics and Business | Universitas Diponegoro, 2024)
This research aims to determine : Influence Employee Engagement and Job Satisfaction To Organizational Citizenship Behavior is mediated by Intention To Stay . Population study is all over Malut Post Ternate City employee amount 47 respondents and use saturated sampling technique so that amount sample as much 47 respondents . Type of data used is quantitative data and the data sources used is primary data with data collection via questionnaire . Deep data analysis models study This use Structural Equation Modeling (SEM) Partial Least Squares ( SmartPLS ) version 4.0 . Research result This show that : (1) employee engagement influential significant to Organizational Citizenship Behavior (OCB) ; (2) Job Satisfaction influential significant on Organizational Citizenship Behavior (OCB) ; (3) employee engagement has no effect significant towards Intention To Stay ; (4) Job Satisfaction influential significant to Intention To Stay ; (5) intention to stay has a significant effect on organizational citizenship behavior ; (6) ) employee engagement does not mediate intention to stay on OCB ; (7) job satisfaction does not mediate intention to stay on OCB.